2007
DOI: 10.1002/ajmg.a.31724
|View full text |Cite
|
Sign up to set email alerts
|

Methylthioadenosine phosphorylase (MTAP) in hearing: Gene disruption by chromosomal rearrangement in a hearing impaired individual and model organism analysis

Abstract: Genes with a role in the auditory system have been mapped by genetic linkage analysis of families with heritable deafness and then cloned through positional candidate gene approaches. Another positional method for gene discovery is to ascertain deaf individuals with balanced chromosomal translocations and identify disrupted or disregulated genes at the site(s) of rearrangement. We report herein the use of fluorescence in situ hybridization (FISH) to map the breakpoint regions on each derivative chromosome of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Early embryonic lethality in mice homozygous for null mutations has been observed for several mouse tumor suppressor genes including Rb , Wt1 , Apc , Nf2 and Brca1 (30). Our findings are also consistent with those published by (31), which also found that Mtap was an essential gene in mice.…”
Section: Discussionsupporting
confidence: 94%
“…Early embryonic lethality in mice homozygous for null mutations has been observed for several mouse tumor suppressor genes including Rb , Wt1 , Apc , Nf2 and Brca1 (30). Our findings are also consistent with those published by (31), which also found that Mtap was an essential gene in mice.…”
Section: Discussionsupporting
confidence: 94%
“…18 The 9p region includes the MTAP gene, which is disrupted by a de novo balanced translocation in a child with syndromic deafness. 19 We sequenced all exons and conserved intronic regions of TMC1 and MTAP in family DE, but did not identify novel variants segregating with deafness in either gene. The DFNA47 locus maps within the DFNB83 region at chr9:13 046 167-21 980 675.…”
Section: Novel Deafness Locimentioning
confidence: 99%
“…More than a decade ago, the Mendelian Cytogenetics Network (MCN) was established to study DBCRs in a systematic fashion (Tommerup 1993;Bugge et al 2000), and, more recently, similar programs to characterize DBCRs have been initiated elsewhere (Alkuraya et al 2006;Lu et al 2007;Williamson et al 2007).…”
Section: Genome Research 1145mentioning
confidence: 99%